The Role of Learning Organs of Speech - Yani Lubis; Nahdiyah Rizqoh Nasution; Amelia Azzahra; Fika Mardiani (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
The ability to speak is a vital aspect of human life, involving the interplay between cognitive processes and the function of speech organs, such as the vocal cords, tongue, teeth, lips, and oral cavity. The articulation process enables humans to produce intelligible sounds for effective communication. This study aims to explore the anatomical, physiological, and phonetic roles of speech organs in generating, varying, and comprehending language sounds, particularly in the context of foreign language learning. A qualitative descriptive approach was adopted, with data gathered through interviews, literature reviews, and document analysis. The study provides an in-depth understanding of the connection between speech organ use and linguistic phenomena such as phonological structures, dialects, accents, and variations. Furthermore, it examines the significance of speech organs in phonetics and phonology learning for both native and second-language learners. The findings contribute to theoretical and applied linguistic studies, especially in phonetic, phonological, and language education analysis.